Life Cycle Cost Concept in Maintenance of Office Building of Karhutla Workshop Uptd Kphp Berau Barat - Rusmin, Rusmin; Oetomo, Wateno; Marleno, Risma (LPPM of NAROTAMA UNIVERSITY, 2025)
In Indonesia, Building Maintenance Guidelines have been stipulated in the Regulation of the Minister of Public Works No. 24/PRT/M/2008 concerning Guidelines for Building Maintenance and Care. The construction of the office building of the KARHUTLA workshop of UPTD KPHP Berau Barat is certain to increase every year, of course it must be followed by good and planned management, not only construction costs but there are important costs that need to be considered as a reference for managers to run and operate the building, namely planning the future costs of the building itself including operational costs, maintenance costs and replacement. The Life Cycle Cost (LCC) method is one part of the building management and maintenance strategy. From the background of the problem, a study was conducted entitled Analysis of Maintenance Based on Life Cycle Cost in the Office Building of the KARHUTLA Workshop of UPTD KPHP Berau Barat. The solution method in this calculation is for Investment Feasibility Analysis using Initial Cost Analysis, Operational Cost Analysis, Maintenance and Care Cost Analysis, Demolition Cost Analysis. From the results of the analysis, it was obtained that there were three groups that compiled the Life Cycle Cost analysis plan for the UPTD Berau Barat workshop building, namely, initial construction costs, operational costs, maintenance costs and demolition costs. The initial construction cost of the UPTD Berau Barat workshop building cost Rp2,515,780,000.00 (48%), operational costs of Rp870,000,000.00 (17%), maintenance and care costs of Rp1,601,275,363.86 (30%), demolition costs of Rp251,178,000.00 (5%). The total Life Cycle Cost of the UPTD Berau Barat workshop building for 25 years is Rp5,234,233,363.86. In operational costs, the largest cost is the utility cost of Rp540,000,000.00 (62%) followed by employee salary costs of Rp330,000,000.00 (38%). In terms of maintenance costs, the largest costs are architectural costs of Rp. 1,433,035,692.66 (92%), followed by mechanical & electrical costs of Rp. 123,719,815.22 (8%).